Brain Abscess: CT vs Non-CT Evaluation and Management - Shah, Azaz Ali (Journal of Postgraduate Medical Institute, 2011)
Brain abscesses are emergencies and should be dealt immediately. In departments where CT scan facilities were available, it is not a big problem; while in periphery clinical judgment, examination and history of the patient and neurological signs will give lot of clues to save his life with simplest of procedures; a burr hole at temporal area.Muhammad Irfan